1977
DOI: 10.1172/jci108688
|View full text |Cite
|
Sign up to set email alerts
|

Relative contributions of large and small airways to flow limitation in normal subjects before and after atropine and isoproterenol.

Abstract: A B S T R A C T Bronchodilatation was produced in normal subjects by the inhalation of atropine, a parasympatholytic agent,.and isoproterenol, a beta adrenergic stimulator. Density dependence of maximal expiratory flow (Vmax) expressed as a ratio of Vmax with an 80% helium-20% oxygen gas mixture to

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
28
1
1

Year Published

1995
1995
2022
2022

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 115 publications
(34 citation statements)
references
References 19 publications
4
28
1
1
Order By: Relevance
“…The result was not expected a priori as it is generally thought that ipratropium produces its bronchodilating effect mainly in the central airways [22,23].…”
Section: Discussionmentioning
confidence: 91%
“…The result was not expected a priori as it is generally thought that ipratropium produces its bronchodilating effect mainly in the central airways [22,23].…”
Section: Discussionmentioning
confidence: 91%
“…If these chemical mediators were the main substances active in small airway responders, small airway responders in the present study would have been more hyperreactive than the large airway responders. From the analysis of maximal expiratory flow-volume curves with inspired gases of different densities, Ingram et al (1977) suggested that in normal subjects the predominant sites of atropine aerosol activity are the central airways and sites of isoproterenol are the peripheral airways. Later, using the concept that changes in anatomic dead space reflect changes in central airway dimension, Hensley et al (1978) reached the same conclusion.…”
Section: Treatment Of Peripheral Airway Hyperreactivitymentioning
confidence: 99%
“…This finding is compatible with the absence of changes in large airway resistance. This was corroborated functionally by normal values of Raw and SGaw in the diabetic group and reinforced the relative preservation of respiratory muscle function since the determinants of these flows are resistance of large airways and muscle effort (33,34).…”
Section: Discussionmentioning
confidence: 66%